‘Every turn can be the last one I do’ - Perceptions of injury risk in high-performance snow sports and its implication for injury prevention - Bonell Monsonís, Oriol; Verhagen, Evert; Spörri, Jörg; Gouttebarge, Vincent; Bolling, Caroline (Injury prevention, 2024)
ObjectivesHigh-performance snow sports (HPSS) athletes compete in a performance-driven context with a high risk of injury. While there is a lack of evidence on effective prevention measures in snow sports, this study explored the perspectives and perceptions of HPSS stakeholders on sports injury prevention.MethodsWe conducted an exploratory qualitative study based on the grounded theory principles through 11 semistructured interviews with athletes, coaches and healthcare providers from different national teams about sports injury prevention. The interviews were inductively analysed through constant comparative data analysis.ResultsParticipants defined risk management as a central concept in which they approached injury prevention by assessing, managing and sometimes accepting risks. Many factors, such as athlete-related and external factors, are considered in this process, ultimately influencing their decision-making. Participants acknowledged the value of experience when managing and dealing with risks, a key aspect of their learning process and career development. Within this context, open and trustworthy communication and shared responsibilities among all stakeholders influenced and shaped injury prevention strategies and behaviours. Understanding and balancing out speed and risks was considered pivotal in their daily practice. Therefore, injury prevention awareness, ownership, communication, teamwork and shared responsibilities may contribute to the success of sports injury prevention in HPSS.ConclusionThese findings substantiate the significance of such contextual factors in sports injury prevention. Considering the high-risk nature of HPSS, injury prevention suggests a shift towards risk management strategies, with a strong emphasis on contextual factors and their interactions. Young athletes might benefit from educational interventions centred on developing skills to assess and manage risks.